Contemporary Debates in Bioethics: European Perspectives - Mihailov, Emilian; Elger, Bernice; Federiuc, Victoria; Mihailov, Emilian; Wangmo, Tenzin (De Gruyter, 2019)
The volume aims to capture a European gist of theoretical sensibilities, conceptual resources, and research interests, but not in an adversarial way, as opposed to American bioethics. The volume gathers contributions from European scholars as they collaborate and form a research network, drawing on a diversity of philosophical traditions and local knowledge, with the aim of debating universal bioethical problems. ABSTRACTING & INDEXING Contemporary Debates in Bioethics: European Perspectives is covered by the following services: Baidu Scholar DOAB (Directory of Open Access Books) EBSCO Discovery Service Google Scholar J-Gate Naviga (Softweco) Primo Central (ExLibris) ReadCube Semantic Scholar Summon (ProQuest) TDOne (TDNet) WorldCat (OCLC)
Keywords: PHILOSOPHY / Ethics & Moral Philosophy; Europe